EFEKTIVITAS PROGRAM DIKLAT TEKNIS SUBTATNTIF DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM DI ACEH - Salman Al Farisi; Farid Wadjidi Ibrahim; Murniati (Unsyiah) (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2022)
Education and Training Center so that the results can provide a general picture regarding the effectiveness of the implementation of the training program. In addition, it is also hoped that the results of this research can be input and improved in the context of improving the implementation of similar training programs that will be implemented in the future. In particular, the focus of this research is directed at measuring the level of effectiveness in three aspects; reaction aspects, learning aspects, and aspects of potential changes in training participants' behavior related to aspects of teacher performance, pedagogic, social, professional, and personality competencies. This research method uses a quantitative approach and a descriptive evaluative method. A quantitative approach is used in collecting information and data needed in research. Then, the research findings are described and interpreted using a descriptive evaluative method. The results showed that the reaction aspect (level 1) of the training participants to the materials, facilities, and infrastructure of the education and training organizers, and Widyaiswara was included in the good category. However, there are still some improvements related to the level of difficulty of the training material, learning support media, and variations in the use of models and learning approach according to the characteristics of the material and problems. The learning aspect (level 2) based on the learning outcomes of the pre-test and post-test scores showed an increase in understanding of the material for the acquisition of an N-gain score of 0.51 in the medium category, while the skills and attitudes of the training participants during the training were in a good category. Potential aspects of behavior change (level 3) related to teacher performance in pedagogic, professional, personality, and social aspects were obtained in a category. However, the results of this study also show that there is still a low level of confidence in several indicators such as the indicator of utilizing ICT for the benefit of PAI learning development and taking reflective action to improve the quality of learning, developing and creatively guided learning materials and sustainably developing professionalism. through reflective action. The low behavior change in these indicators is due to the low understanding and skills of using ICT because they are not accustomed to using it, and the heavy workload of teachers is the reason for not having time to make self-development efforts.